Factors characterizing stages of change for smoking during pregnancy: General risk knowledge, personal risk perceptions, motives, reasons and decisional balance. - Allston, Julie. (University of Ottawa (Canada), 1995)
A secondary analysis of data from a sample of pregnant smokers is described, which focuses on examining knowledge, attitudes and beliefs related to women's decision to continue smoking during pregnancy. Pregnant women are examined at each of the first three stages of change: women not considering quitting in the next six months (Precontemplation), women considering cessation in this time frame (Contemplation), and women planning on stopping smoking in the next 30 days (Preparation). Pregnant women (n = 2461) were surveyed in a cross-sectional convenience sample of prenatal clinic attendees in a city of approximately 350,000 people, over a one-year period. 32% of pregnant smokers were in the Precontemplation stage, 35% in Contemplation, and 33% in Preparation. In general, participants' level of knowledge was high about maternal and fetal risks of smoking during pregnancy. However, similar items assessing personal perceptions of risk showed that many women thought their personal risk was lower than pregnant smokers in general. Negative affect was the dominant motive, and Level 1 reasons (doubting the evidence of harm) were cited as being most important factors related to continued smoking. Overall, participants gave higher ratings to the cons of smoking than to the pros. Women in Preparation had significantly higher knowledge of risks from smoking during pregnancy than Contemplators, but did not differ significantly from Precontemplators, while Precontemplators did not differ significantly from Contemplators on this variable. Women in Preparation had a significantly higher personal perception of risk for the fetus of smoking during pregnancy than women in the other two stages. As expected, Precontemplators perceived significantly lower Cons of smoking than women in the other two stages, who did not differ significantly from each other. (Abstract shortened by UMI.)
Keywords: Health Sciences, Obstetrics and Gynecology.